ANALISIS YURIDIS TERHADAP KEABSAHAN SURAT PEMANGGILAN RAPAT UMUM PEMEGANG SAHAM - Hutagalung, Jessica Imelda Putri; Siregar, Mahmul; Robert, Robert (Smart Education, 2025)
Abstract:A GMS canbeheldifmorethan 1/2 (half) ofthe total numberofshareswith voting rights are presentorrepresented in the GMS, unlessthelawand/orarticlesofassociationdetermine a largerquorum. If thequorumrequirement in the GMS summonsis not achieved, a second GMS summonscanbemade. If thequorumforthesecond GMS isalso not achieved, thecompanycanrequestthechairmanoftheDistrictCourttodeterminethequorumforthethird GMS. Thisthesisisentitled